Bactericidal efficacy of plasma-activated water against Vibrio parahaemolyticus on Litopenaeus vannamei - Zhang, Huanlan; Wei, Jie; Xv, Hongjie; Khan, Imran; Sun, Qinxiu; Zhao, Xihong; Gao, Jialong; Liu, Shucheng; Wei, Shuai (Frontiers in Nutrition, 2024)
In this study, the antimicrobial mechanism of plasma-activated water (PAW) against Vibrio parahaemolyticus and the effectiveness of PAW in artificially contaminated Litopenaeus vannamei were investigated. The results demonstrated a significant reduction (p < 0.05) in viable counts of V. parahaemolyticus with increasing plasma discharge time (5, 10, 20 and 30 min) and PAW immersion time (3, 5, 10, 20 and 30 s).Specifically, the count of V. parahaemolyticus decreased by 2.1, 2.7, 3.3, and 4.4 log CFU/mL after exposed to PAW 5, PAW 10, PAW 20, and PAW 30 for 30 s, respectively.Significant cell surface wrinkling, accompanied by notable nucleic acid and protein leakage were observed after treatment with PAW. The permeability of the inner and outer cell membranes was significantly increased (p < 0.05), along with an increase in electrical conductivity (p < 0.05). The reactive oxygen species (ROS) within V. parahaemolyticus cells were significantly increased (p < 0.05), while superoxide dismutase (SOD) activity, and the relative expression of the ompW, emrD, and luxS genes were significantly decreased (p < 0.05). A reduction number of 1.3, 1.8, 2.1, and 2.2 log CFU/g of V. parahaemolyticus in artificially contaminated L. vannamei was obtained with PAW for 5 min. The study elucidated that PAW could destroy cell membranes, leading to cell death. The findings would strengthen strategies for V.parahaemolyticus control and provide a potential application of PAW for preserving aquatic products.